2014
DOI: 10.3109/02699206.2014.927002
|View full text |Cite
|
Sign up to set email alerts
|

“Measuring up” to ethical standards in service delivery to college students on the Autism Spectrum: A practical application of Powell’s model for ethical practices in clinical phonetics and linguistics

Abstract: This paper examined an interdisciplinary college-based support programme, the Communication Coaching Program (CCP), designed for students diagnosed on the autism spectrum in light of six ethical constructs described by Powell. Collecting data to monitor the successes and ongoing needs of individual participants in the programme is of vital importance, of course, but only addresses a portion of the efficacy question. In addition, the authors, who co-direct the programme and represent different professional expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…According to Cavanagh and Grant (2006), this is the qualitatively best design for quantitative outcome research and extremely difficult to achieve. In comparison, many studies have used single group or pre-post within-subject designs (e.g., Olivero et al, 1997;Grant, 2003;Jones et al, 2006;Orenstein, 2006). By using this research design, we showed that as few as nine units over three face-to-face coaching sessions can be effective in reducing IP scores, extending previous work finding effective short-term interventions (e.g., Burke and Linley, 2007;Grant, 2009).…”
Section: Limitations Strengths and Future Researchsupporting
confidence: 73%
“…According to Cavanagh and Grant (2006), this is the qualitatively best design for quantitative outcome research and extremely difficult to achieve. In comparison, many studies have used single group or pre-post within-subject designs (e.g., Olivero et al, 1997;Grant, 2003;Jones et al, 2006;Orenstein, 2006). By using this research design, we showed that as few as nine units over three face-to-face coaching sessions can be effective in reducing IP scores, extending previous work finding effective short-term interventions (e.g., Burke and Linley, 2007;Grant, 2009).…”
Section: Limitations Strengths and Future Researchsupporting
confidence: 73%